Primary apocrine carcinoma of the axilla in a male patient: a case report - Zahid, Rehan (Clin Case Rep, 2016)
Primary apocrine sweat gland carcinoma is a rare neoplasm. It is usually slow growing and is often suspected to be a benign disease at initial assessment. A thorough clinical and histological workup is required for diagnosis. Treatment of choice is wide local excision with clear margins.